Bio-Based Disposable Containers for Food Services - Barretto, Roselle; Qi, Guangyan; Jones, Christopher; Li, Yonghui; Sun, Xiuzhi Susan; Wang, Donghai (Advances in polymer technology, 2024)
Currently, petrochemical plastics dominate the food service industry due to their good mechanical properties and barrier against heat, water vapor, carbon dioxide, and oxygen. This widespread use is not only harmful to humans but also to the ecosystem as synthetic plastics disrupt ecological balance and deplete petroleum-based oil resources. Researchers and manufacturers are continuously addressing this problem by developing bio-based alternatives that provide numerous advantages including structural flexibility, biodegradability, and effective barrier properties. However, the high cost of production and unavailability of equipment for batch processing impede the potential for widespread manufacturing. Natural fibers mixed with bio-based adhesives derived from plants provide one of the biggest potential sources of bio-based materials for the food container industry. Not only does this address the issue of high raw material cost but it also has the potential to become sustainable once processing steps have been optimized. In this review, the current findings of several research related to the production of bio-based disposable food containers, packaging, and composites made from bio-based materials and bio-based adhesives are critically discussed. Several properties and characteristics important to the production of food service containers and primary packaging, as well as the existing challenges and future perspectives, are also highlighted.